Medan Makna Aktivitas Gerakan Tangan Dalam Bahasa Gorontalo - Zakaria, Ulfa (CV. Multi Kreasi Media, 2023)
An inventory of the field of meaning of hand movement activities in the Gorontalo language is intended as one of the first steps in documenting a language that is in danger of extinction. This research was conducted with a qualitative descriptive method. Data was obtained through collecting information from existing written documents and supplemented by checking its use among Gorontalo speakers. Analysis of the data was carried out based on the theory of componential analysis of the meaning of hand movement activities which included hand movements in a flicking position, closed palms and open palms. The semantic function of the three groups of hand movements refers to hand movements aimed at touching, either with pressure or not, and directed at body parts and objects around the speaker.